Novel Anti-Platelets in Stable Coronary Artery Disease - Papageorgiou, Nikolaos; Zacharia, Effimia; Ioannou, Adam; Rehal, Onkar; Zacharias, Konstantinos; Siasos, Gerasimos; Tousoulis, Dimitris (Current Pharmaceutical Design, 2016)
Background: Apart from the acute thrombotic complications that lead to acute coronary syndromes (ACS), platelet activation also plays an important role in the initiation and progression of atherosclerosis. In addition, it is speculated that anti-platelet therapy can be beneficial for patients with stable coronary artery disease (CAD). Of note, patients on optimal anti-platelet treatment still experience thrombotic events, whereas complications, such as bleeding, cannot be ignored. In this light, novel antiplatelet regimens have been used to minimize the residual platelet activation without compromising normal haemostasis. Methods: We performed a thorough search of the literature in order to review the beneficial role of novel antiplatelets in patients with stable CAD. We have also focused on studies that examine the effect of these drugs on platelet reactivity as well as on cardiovascular outcomes. Conclusion: Specific agents, such as vorapaxar and cilostazol, have been found to reduce platelet reactivity as well as to improve patients’ prognosis. Of note, the use of novel antiplatelets is of clinical importance in patients with increased thrombotic status and in those with resistance to classic antiplatelets. However, the available data on most of the novel antiplatelets are mainly derived from studies including ACS patients undergoing angioplasty Therefore, large randomized controlled studies are required to evaluate the clinical benefit of novel antiplatelets in patients with stable CAD.
Keywords: stable coronary artery disease